2021
DOI: 10.1002/smll.202103590
|View full text |Cite
|
Sign up to set email alerts
|

De Novo Engineering of Metal–Organic Framework‐Printed In Vitro Diagnostic Devices for Specific Capture and Release of Tumor Cells

Abstract: monitoring of disease progression and treatment efficacy. [1] The efficient enrichment of biomarkers with high sensitivity and specificity is usually required for IVDs; however, the complex nature of body fluids (i.e., cell debris, normal blood cells, etc.) may hinder selective biomarker capture. [2] Moreover, the material capture mechanism may induce unrecoverable changes to biomarkers, affecting its accuracy. [2] Therefore, the choice of materials which enable efficient capture of native biomarkers with good… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 55 publications
(53 reference statements)
0
3
0
Order By: Relevance
“…14 MOFs, constructed from metal ions or metalcontaining clusters and organic linkers, possess versatile functionality, tunable pore size, well-dened pore aperture, tailorable composition, and structure. [15][16][17][18][19] These properties are particularly advantageous for controlling molecular transport through coatings. [20][21][22][23][24] MOF coatings can be formed around living cells through in situ or post-loading strategies.…”
Section: Introductionmentioning
confidence: 99%
“…14 MOFs, constructed from metal ions or metalcontaining clusters and organic linkers, possess versatile functionality, tunable pore size, well-dened pore aperture, tailorable composition, and structure. [15][16][17][18][19] These properties are particularly advantageous for controlling molecular transport through coatings. [20][21][22][23][24] MOF coatings can be formed around living cells through in situ or post-loading strategies.…”
Section: Introductionmentioning
confidence: 99%
“…However, the wide industrial utilization of enzymes is hindered by their fragile nature, such as low tolerance to most organic solvents and digestive cocktails, narrow optimum pH ranges, and low thermal stability, which easily leads to a decreased enzymatic activity . In the past few years, metal–organic frameworks (MOFs) have attracted wide interest for enzyme immobilization. Composed of metal nodes and organic ligands, MOFs and their subclass zeolitic imidazolate frameworks (ZIFs) exhibit diverse chemical and structural features (such as shape, pore size, surface area, and structural flexibility). These versatile features enable MOFs as an inert host as well as tailor the selectivity, stability, and/or activity of the enzymes while protecting them from unfavorable environments. However, upon immobilization in MOFs, most enzymes experience a decreased activity due to the restricted enzyme conformation and substrate accessibility. Until now, increasing the pore size and creating hollow cavities within MOFs have been the most popular strategies to improve the biocatalytic MOF activity.…”
Section: Introductionmentioning
confidence: 99%
“…To this point, zeolite imidazole frameworks (ZIFs), including ZIF-8, ZIF-90, MAF-7, and so forth, are the favorable MOF matrices for enzyme immobilization due to their biocompatible synthesis conditions. A pioneering work by Liang, Falcaro, and co-workers has found that ZIF-8 could in situ crystallize around a given enzyme, analogous to the natural biomineralization . Utilizing this method, single or multiple enzymes are readily encapsulated into ZIFs, and the encapsulated enzymes display improved stability yet maintain desirable bioactivity. However, these ZIFs biohybrids are microcrystalline powders and hence are difficult to be mechanically processed and shaped in a controllable manner. This significantly limits the MOF biohybrid acting as the core element in large-scale industrial applications, such as portable biosensors.…”
mentioning
confidence: 99%